IDENTIFIKASI KESULITAN SISWA DALAM MEMAHAMI KONSEP DASAR MATEMATIKA DI SEKOLAH DASAR NEGERI MODEL TERPADU MADANI PALU - Ammar, Ammar Abdullah Joni Guci; Khairunnisa; Sukri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to obtain information related to the factors of students' difficulty in understanding basic mathematical concepts in grade IV students of SDN Model Terpadu Madani Palu. This research was conducted on Classroom Teachers in grade IV. The method used is a qualitative descriptive research method with data collection techniques through interviews with classroom teachers and related literature studies carried out using source triangulation. Based on the results of the analysis, it was concluded that the difficulty factor for students in understanding basic mathematical concepts was caused by two factors, namely internal factors and external factors. Internal factors include low motivation to learn and lack of mastery of prerequisite concepts, as well as external factors including less varied learning methods and limited learning time